A new modern book on electrolyte solutions - Holovko, M.F. (Condensed Matter Physics, 2000)
Review: J.Barthel, H.Krienke, W.Kunz. Physical Chemistry of Electrolyte Solutions: Modern Aspects. Steinkopff, Darmstadt and Springer, New York, 1998, 401 p.)